Halal Certification Systems: A Comparison Between Indonesia and Turkey - Nurul Fibrianti; Aprila Niravita; Sang Ayu Putu Rahayu; Ratih Damayanti; Ayup Suran Ningsih (Universitas Negeri Semarang, 2023)
Ensuring the halal status of a product involves utilizing the services of a halal certification body, offering legal protection and confidence in halal product assurance for Muslim consumers. Indonesia is currently in the process of transitioning the certification authority from the non-governmental organization MUI to the government agency BPJPH under the Ministry of Religious Affairs. The halal certification mechanism through BPJPH closely aligns with the established process carried out by MUI. Similarly, Turkey has established the Halal Accreditation Authority (HAK) to guarantee the legal certainty of halal products, providing accreditation services for halal conformity assessment agencies. This study uses a descriptive method with a comparative approach. Focuses on positive legal nor governing the implementation of halal product between Halal Prodyct Assurance (JPH) and Halal Accreditation Authority (HAK). The findings reveal that in order to implement the Halal Product Assurance (JPH) system, the Indonesian government established the Halal Product Assurance Organizing Agency (BPJPH). The establishment of a globally recognized halal certification system and the removal of trade barriers in halal goods and services require the effective execution of responsibilities, as demonstrated by Turkey through the activities of the Halal Accreditation Authority (HAK). Turkey's strategy for ensuring the genuineness of halal products involves the Halal Accreditation Authority, tasked with evaluating, accrediting, and supervising the competence of halal conformity assessment bodies. This procedural framework aligns with both national regulations and international standards, incorporating additional technical regulations specified in the accreditation body's implementation documents.